Single-chain antibody-mediated intracellular retention of ErbB-2 impairs Neu differentiation factor and epidermal growth factor signaling. - Graus-Porta, D (1995)
ErbB-2 becomes rapidly phosphorylated and activated following treatment of many cell lines with epidermal growth factor (EGF) or Neu differentiation factor (NDF). However, these factors do not directly bind ErbB-2, and its activation is likely to be mediated via transmodulation by other members of the type I/EGF receptor (EGFR)-related family of receptor tyrosine kinases. The precise role of ErbB-2 in the transduction of the signals elicited by EGF and NDF is unclear. We have used a novel approach to study the role of ErbB-2 in signaling through this family of receptors. An ErbB-2-specific single-chain antibody, designed to prevent transit through the endoplasmic reticulum and cell surface localization of ErbB-2, has been expressed in T47D mammary carcinoma cells, which express all four known members of the EGFR family. We show that cell surface expression of ErbB-2 was selectively suppressed in these cells and that the activation of the mitogen-activated protein kinase pathway and p70/p85S6K, induction of c-fos expression, and stimulation of growth by NDF were dramatically impaired. Activation of mitogen-activated protein kinase and p70/p85S6K and induction of c-fos expression by EGF were also significantly reduced. We conclude that in T47D cells, ErbB-2 is a major NDF signal transducer and a potentiator of the EGF signal. Thus, our observations demonstrate that ErbB-2 plays a central role in the type I/EGFR-related family of receptors and that receptor transmodulation represents a crucial step in growth factor signaling.